Immanuel Kant in the Historical Philosophy of Gustav Shpet - Tatiana G. Shchedrina; Irina O. Shchedrina (Кантовский сборник, 2022)
This article assesses the role of Immanuel Kant’s ideas in the historical philosophy of Gustav Shpet (1879—1937). This theme has been largely ignored by Shpet scholars who have concentrated on comparing his logical-methodological theories with the ideas of representatives of phenomenology (E. Husserl, R. Ingarden and others) and hermeneutics (F. Schleiermacher, W. Dilthey, H. Lipps, H.-G. Gadamer and others). Accordingly, the authors consistently reconstruct “the sphere of conversation” within which Shpet’s concept of “historical philosophy” was formed and reveal the place and role of Kant’s ideas in Shpet’s theories (with particular focus on the Plato-Kant antithesis). Among Shpet’s “interlocutors” with whom he discusses Kant and thus “ploughs” the field of historical philosophy are G. I. Chelpanov and E. Husserl, B. Bolzano and A. Trendelenburg, F. Heman and M. Frischeisen-Kohler. We have attached Shpet’s notes on Kant in the archive of his family. Shpet’s attitude to Kant was controversial (while of course largely critical) and yet he was aware that Kant was the foundation of European philosophy and that his efforts to resolve the epistemological problem merit a second, thorough examination and a retracing of the path followed by Kant. The authors show that Shpet’s notes on Kant have more than historical-philosophical relevance. They enable us to take a new look at many theoretical and cognitive problems and, even more importantly, make us rethink the fundamental tenets of philosophy and the methodology of scientific cognition.